EXTRA FLEXIBLE TACTICAL CABLE. - Rigling, W. S. (1966)
This document reports a program to develop a family of lightweight, small diameter, highly flexible, multiconductor cables to meet current and anticipated operational requirements of Army equipment in Arctic and tropical environments. The cables shall be air transportable, and suitable for use with widely dispersed and highly mobile tactical equipments. The evaluation of various cable components (binders, shields, insulating and jacketing materials) and preliminary designs have been completed. (Author)